2016
DOI: 10.1002/aoc.3507
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine functionalized‐silica palladium (II) complex: a highly efficient, environmentally benign and recyclable nanocatalyst for C‐C bond forming reactions under mild conditions

Abstract: An environmentally friendly silica‐grafted nicotine‐based palladium(II) complex was successfully prepared and evaluated for the first time as novel and efficient nanocatalyst in C‐C bond forming reactions. Grafted‐nicotine in this catalytic system plays an important role, and as an effective ligand and a quaternary ammonium salt demonstrates an efficient stabilizing effect on the Pd(II) species by a synergistic effect of coordination and electrostatic interactions. The catalyst was well characterized by FT‐IR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Based on the optimal condition, different aryl bromides reacted with phenylacetylene and afforded the corresponding Sonogashira products ( Scheme 73 ). 132 …”
Section: Application Of the Pd-catalyzed Sonogashira Reactions In The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the optimal condition, different aryl bromides reacted with phenylacetylene and afforded the corresponding Sonogashira products ( Scheme 73 ). 132 …”
Section: Application Of the Pd-catalyzed Sonogashira Reactions In The...mentioning
confidence: 99%
“…Based on the optimal condition, different aryl bromides reacted with phenylacetylene and afforded the corresponding Sonogashira products (Scheme 73). 132 A nano tetramine palladium(0) complex catalyst was efficiently used as an effective heterogeneous catalyst in the Cu-free Sonogashira coupling reaction in DMF. Analysis of the reaction mixture demonstrated that the leaching of Pd from the catalyst was insignicant.…”
mentioning
confidence: 99%
“…Hajipour and co‐workers illustrated a silica‐grafted nicotine‐based Pd(II) complex 31 for Sonogashira coupling (Figure 5). [ 94 ] The grafted‐nicotine acts not only as an effective ligand, but also a quaternary ammonium salt. It is believed that the grafted‐nicotine gives a stabilizing effect on the Pd(II) species by a synergistic effect of coordination and electrostatic interactions.…”
Section: Classical Sonogashira Coupling Reactionsmentioning
confidence: 99%
“…Silica matrices including functionalized silica gel, silica yolk–shell, nanoporous silica, SBA-15, SBA-16, MCM-41, MCM-48, SiO 2 aerogels, silica wet gel, fluorous silica gel, and organosilicas have been used to support PdNPs on their surfaces. These materials are utilized in Suzuki–Miyaura, Heck, and Sonogashira cross-coupling reactions because they possess excellent reactivities under sustainable conditions and can be readily recovered and reused by simple filtration after completion of the reaction.…”
Section: Introductionmentioning
confidence: 99%